2021
DOI: 10.3389/fpsyg.2021.705655
|View full text |Cite
|
Sign up to set email alerts
|

Father’s Perspectives on Family Relationships and Mental Health Treatment Participation in the Context of Maternal Postpartum Depression

Abstract: Objective: To understand the perspectives of fathers whose partners experienced postpartum depression, particularly (1) views on how fathers and family relationships were impacted by maternal PPD, and (2) attitudes regarding inclusion of fathers within the treatment process.Methods: We conducted qualitative interviews with 8 postpartum couples using a semi-structured protocol, and administered questionnaires assessing demographics, depression, and family functioning. We abstracted data from hospital records re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…He would spend more time at work, finding it difficult to articulate his feelings with his therapist and wife (Hernandez et al, 2022). Another study found that fathers had difficulty understanding postpartum mental health conditions while experiencing a wide range of difficult emotions for them to articulate (Battle et al, 2021). Experiences of paternal PPD are characterized by the inability to cope, emotional lability, and dysphoria, making it increasingly challenging for these fathers to enable adaptive coping techniques (Letourneau et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…He would spend more time at work, finding it difficult to articulate his feelings with his therapist and wife (Hernandez et al, 2022). Another study found that fathers had difficulty understanding postpartum mental health conditions while experiencing a wide range of difficult emotions for them to articulate (Battle et al, 2021). Experiences of paternal PPD are characterized by the inability to cope, emotional lability, and dysphoria, making it increasingly challenging for these fathers to enable adaptive coping techniques (Letourneau et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the interaction between parents' mental health statuses may accentuate PPD symptoms in the mother [4]. And the father may influence the mother's likelihood of PPD through their communication quality, relationship satisfaction, and social support [5,6]. PPD knowledge, coping skills, and mental health attitudes can also influence the father's ability to aid the mother in preventing PPD [7].…”
Section: Introductionmentioning
confidence: 99%
“…How confident are you that you will be able to [were able to] help your partner cope with mental health struggles after the baby is [was] born?4 How prepared to you think you are [were] for these changes? (i.e., all physical, mental, relational changes that may occur postpartum)5 Perceived Stress Scale6 How do you think your relationship will [did] change after the baby is [was] born? A lot worse -a lot better…”
mentioning
confidence: 99%